Judy Moody : Around the World in 8 1/2 Days - McDonald, Megan; Reynolds, Peter (Cambridge, Mass. : Candlewick Press, 2006)
Judy Moody's new friendship with Amy Namey causes problems with her old friends and the school project they are working on together.
Keywords: Friendship -- Fiction; Schools -- Fiction; Friendship -- Fiction; Schools -- Fiction